2006
DOI: 10.2174/156802606775270297
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibitors of Inducible Nitric Oxide Synthase: Potential Agents for the Treatment of Inflammatory Diseases?

Abstract: Nitric Oxide (NO) is widely recognized as an important messenger and effector molecule in a variety of biological systems. There is strong evidence from animal models that elevated or lowered NO levels are associated with a variety of pathological states. In nature, NO is synthesised from the amino acid l-arginine by a small family of closely related oxygenase enzymes: the nitric oxide synthases (NOS). A number of studies in animals have associated excessive NO production by one of these enzymes--the inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 153 publications
(201 reference statements)
2
70
0
Order By: Relevance
“…In addition, a significantly decreased expression of iNOS, a key enzyme required for the synthesis of the inflammatory agent NO, and a markedly decreased production of NO itself, is observed in peritoneal macrophages from Elocalcitol-treated NOD mice with established EAP. A number of studies have associated excessive NO production with acute and chronic inflammation in model systems, and have also demonstrated that administration of NO synthase inhibitors can induce beneficial anti-inflammatory effects (58). The capacity of Elocalcitol to inhibit iNOS expression and NO production may thus represent an additional mechanism explaining its anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a significantly decreased expression of iNOS, a key enzyme required for the synthesis of the inflammatory agent NO, and a markedly decreased production of NO itself, is observed in peritoneal macrophages from Elocalcitol-treated NOD mice with established EAP. A number of studies have associated excessive NO production with acute and chronic inflammation in model systems, and have also demonstrated that administration of NO synthase inhibitors can induce beneficial anti-inflammatory effects (58). The capacity of Elocalcitol to inhibit iNOS expression and NO production may thus represent an additional mechanism explaining its anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…(Rod and Brooks, 2003;Wang et al, 2006;Chen et al, 2007;Mauldin et al, 2009) eNOS is an important pharmaceutical target, yet only the neuronal and inducible isoforms of NOS can be specifically inhibited, mainly at the level of their hemodomains. (Tinker and Wallace, 2006;Bonnefous et al, 2009;Silverman, 2009) The dihydrofolate reductase is a key enzyme in cell growth and metabolism. DHFR presents a large pharmacological interest and is the target of methotrexate used for treatments of cancer and infections.…”
Section: Introductionmentioning
confidence: 99%
“…3 A third NOS isoform, inducible NOS (iNOS), plays an important role in the defense against pathogens and is expressed in several cells and tissues, including endothelial and vascular smooth muscle cells, 4 in response to pro-inflammatory stimuli such as bacterial endotoxins (LPS), and/or different cytokines and interleukins. 5 In contrast to the regulated production of NO by eNOS and nNOS, iNOS may generate large amounts of NO over long periods of time, if substrate and cofactors are not limited. 4 In the vascular system, the excessive amount of NO produced by iNOS is associated with decreased function of eNOS and subsequent impairment of both vasoconstriction and endothelium-dependent vasorelaxation.…”
mentioning
confidence: 99%